Визначення факторів, що впливають на стратегічну стійкість підприємства - Клюс, Ю.І.; Стрюк, О.С. (Вісник економічної науки України, 2022)
Саме по собі наявності виявлених факторів стратегічної стійкості замало задля її забезпечення. Отримання конкурентної переваги залежить від того, наскільки ефективно вони використовуються у практичній діяльності підприємства. Функціонуючи в ринковій системі економіки, кожне підприємство має швидко реагувати на будь-які інформацію, зміни, що відбуваються в житті країни. Навряд чи якесь виробництво в нашій країні при переході до ринкової системи господарювання обійшлося без докорінних змін у всіх системах управління. Схема управління, що успішно працювала в умовах централізованого планування, не змогла забезпечити стабільну роботу підприємств у ринкових умовах. І тому структура управління, що покликана відповідати новим принципам маркетингу, зазнала багато змін. Необхідність підвищення ефективності виробництва, його інтенсифікації поставили перед підприємствами завдання подальшого вдосконалення управлінської діяльності. У сучасних умовах відбувається посилення конкуренції, унаслідок чого керівники підприємств перебувають у постійному пошуку нових (адекватних умовам конкуренції) інструментів управління підприємствами та важелів підвищення їхньої стратегічної стійкості. By itself, the presence of identified factors of strategic stability is not enough to ensure it. Obtaining a competitive advantage depends on how effectively they are used in the practical activities of the enterprise. Functioning in the market system of the economy, every enterprise must quickly respond to any information and changes occurring in the life of the country. Hardly any production in our country during the transition to the market economic system did without fundamental changes in all management systems. The management scheme, which worked successfully under conditions of centralized planning, could not ensure the stable operation of enterprises in market conditions. And that is why the management structure, designed to meet new marketing principles, has undergone many changes. The need to increase the efficiency of production, its intensification, set before the enterprises the task of further improvement of management activities. In modern conditions, competition is intensifying, as a result of which enterprise managers are constantly searching for new (adequate to the conditions of competition) enterprise management tools and levers for increasing their strategic stability.
Among the main opportunities for increasing the strategic sustainability of this business element, we can highlight: building a development strategy, creating intangible assets, growth based on competencies, knowledge, technologies, and business processes.
The market allows full manifestation of economic independence, therefore it is our fourth element of modern business. We consider the possibilities of using the market situation from the types of markets (growing, unchanged, stagnant, underdeveloped): survival based on strategic stability in the conditions of "consumer" competition and producer competition.
Despite the importance of all groups of opportunities, a special role at the stage of business development should be attributed to the group of opportunities for strengthening strategic stability with the help of internal resources of the enterprise. This fact is explained by the fact that in today's rapidly changing technological world, the survival of an enterprise largely depends on the quality of its labor resources (personnel), possession of accurate and timely information, created by the infrastructure of business and scientific and technical ideas and material forms of their implementation, that is, the unity of material and immaterial production.